A recommendation for the use of electrical biosensing technology in neonatology - Van Wyk, Lizelle; Austin, Topun; Barzilay, Bernard; Bravo, Maria Carmen; Breindahl, Morten; Czernik, Christoph; Dempsey, Eugene; de Boode, Willem-Pieter; de Vries, Willem; Eriksen, Beate Horsberg; Fauchére, Jean-Claude; Kooi, Elisabeth M. W.; et al. (Pediatric research, 2024)
Non-invasive cardiac output monitoring, via electrical biosensing technology (EBT), provides continuous, multi-parameter hemodynamic variable monitoring which may allow for timely identification of hemodynamic instability in some neonates, providing an opportunity for early intervention that may improve neonatal outcomes. EBT encompasses thoracic (TEBT) and whole body (WBEBT) methods. Despite the lack of relative accuracy of these technologies, as compared to transthoracic echocardiography, the use of these technologies in neonatology, both in the research and clinical arena, have increased dramatically over the last 30 years. The European Society of Pediatric Research Special Interest Group in Non-Invasive Cardiac Output Monitoring, a group of experienced neonatologists in the field of EBT, deemed it appropriate to provide recommendations for the use of TEBT and WBEBT in the field of neonatology. Although TEBT is not an accurate determinant of cardiac output or stroke volume, it may be useful for monitoring longitudinal changes of hemodynamic parameters. Few recommendations can be made for the use of TEBT in common neonatal clinical conditions. It is recommended not to use WBEBT to monitor cardiac output. The differences in technologies, study methodologies and data reporting should be addressed in ongoing research prior to introducing EBT into routine practice.